Landscape context and local-scale environmental influences on the regeneration of tree species in neotropical forests treefall gaps - Grau, Hector Ricardo (2004)
Composition of pioneer species was recorded in 23 to 76  treefalls in the forests of La Selva (LS), Barro Colorado Island (BCI), Cocha Cashu Research Station (CC) and Km41, in order to evaluate the hypothesis that distance to secondary forests which can act as seed sources influences the composition of pioneer tree species at scales of thousands of hectares, and to assess the relative importance of distance to seed sources compared to two microenvironmental factors: soil and gap size. Discriminant Function Analysis (DFA) was used to assess the relative importance of the landscape and environmental factors in controlling the presence in Gaps of Cecropia species that are typical of secondary forests originated in large-scale disturbances. Principal Component Analysis (PCA) was used as an ordination technique based on pioneer species composition of each gap. The PCA ordination axes were regressed against the soil, size, and forest type and distance values of each site in order to explore the relationship between composition and control factors. In the four sites, the variable best correlated to the discriminant function of gaps with and without Cecropia was the distance to secondary forests, although such discriminant function was statistically significant in only one site.  In three of the four sites (with the exception of BCI where there are no typical young secondary forests), distance to secondary forests was correlated with at least one of the axes of the PCA at significance levels < 0.06. Other significant correlations included soil variables (CC and Km 41), gap size (Km 41) and forest type (secondary vs primary, BCI). Overall, the results provide some support for the hypothesis that at the spatial scale of this study, distance to forests originated in large scale disturbances (both natural and anthropogenic) have an influence on treefall gap composition comparable to endogenous and exogenous microenvironmental factors.